Financing decisions : is the quality of information still relevant to be considered? - Arif Budi Satrio, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Information asymmetry makes it difficult for company management to make decisions regarding funding sources. This study aims to investigate and explain the behaviour of company management when faced with asymmetric information problems. Data on 459 companies in Indonesia during the 2005–2019 period are surveyed in an attempt to provide the latest evidence regarding this issue. Investigations using the fixed-effect model approach and dynamic two-step system generalised method of moments are carried out using preliminary and robustness tests. The results show that in addition to company-specific factors, the problem of asymmetric information is an important factor considered by management in determining funding sources. The worsening information gap has led companies to increasingly use external funding from borrowing instead of adding additional funding sources from equity issuance (confirming the pecking order theory). Robust results in this study will be of use to regulators and enrich the literature related to corporate funding decisions in developing countries.